2017
DOI: 10.1016/j.jss.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

pH modulation ameliorates the red blood cell storage lesion in a murine model of transfusion

Abstract: Introduction Prolonged storage of packed red blood cells induces a series of harmful biochemical and metabolic changes known as the red blood cell storage lesion. Red blood cells are currently stored in an acidic storage solution, but the effect of pH on the red blood cell storage lesion is unknown. We investigated the effect of modulation of storage pH on the red blood cell storage lesion and on erythrocyte survival after transfusion. Methods Murine pRBCs were stored in Additive Solution-3 (AS3) under stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Treatment for MAlk are discussed in section 3.3.2. Finally, a study in mice suggests that raising the pH of stored blood enhances red blood survival after transfusion [368] . The pH-dependence of wound healing suggests that therapeutic maintenance of the pH of the wound or graft could aid healing [366] .…”
Section: Other Applications By Clinical Specialtymentioning
confidence: 99%
“…Treatment for MAlk are discussed in section 3.3.2. Finally, a study in mice suggests that raising the pH of stored blood enhances red blood survival after transfusion [368] . The pH-dependence of wound healing suggests that therapeutic maintenance of the pH of the wound or graft could aid healing [366] .…”
Section: Other Applications By Clinical Specialtymentioning
confidence: 99%
“…Stored RBCs undergo considerable shape change from a normal smooth discoid shape (discocyte) to a spheroid shape with speculae (echinocyte). While some of these changes are reversible, others are irreversible, thus making the RBC dysfunctional [ 15 , 16 ]. In our studies, we found that the percent of normal RBCs were higher on Day 56 in RBC stored in VitC ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hemolysis was intensified in erythrocytes obtained from glucose-6-phosphate dehydrogenase (G6PD) deficient patients. Of importance in this work, erythrocytes were salvaged in Zhang’s work and in reports by others [ 14 ] by the addition of antioxidants, by alterations of pH [ 15 ] or by addition of alkaline CPD, which preserves erythrocyte 2,3-DPG. [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that alkalinization would be protective. Chang et al 30 found that, compared to standard AS‐3 with pH 5.8, acidification (pH 4.5) shortened circulating half‐life, while alkalinization (pH 8.5) increased circulating half‐life and decreased hemolysis. Alkalinization likely contributes to the prolonged blood storage capacity of AS‐7 vs AS‐1 31 .…”
Section: Discussionmentioning
confidence: 99%